Impact of sugar palm agroecosystems on herbivorous pests and predatory insects - Heriza, Sri; Ikhsan, Zahlul; Safitri, Aisyah; Pradetia, Pradetia (Universitas Trunojoyo Madura, 2025)
The main product of the palm plant is sap, which results from tapping the male flowers into palm sugar, soft drinks, vinegar, and alcohol. Apart from that, sugar palm plants can also produce food products such as palm fruit from female fruit, sugar palm flour for food in the form of cakes, bread, and biscuits, which comes from processing the pith of the plant stem and can be used as a source of bioethanol production. However, there is limited research on how sugar palm agroecosystems influence the dynamics of herbivorous pests and predatory insect populations, making it essential to understand these interactions for sustainable plantation management. This research aimed to study the influence of sugar palm agroecosystems on the presence of herbivorous insect pests and predatory. The research was conducted in Nagari Labuah Gunung, Lima Puluh Kota Regency, West Sumatra Province. Observations were conducted on stretches of sugar palm plants aged 7-8 years or already producing. The sample plants were determined using purposive sampling, and labels were given to each tree that was part of the sample plants. Identify herbivorous and predatory insects obtained from the field and calculate the attack level. From the research carried out, it was found that management of sugar palm plants affects the presence of herbivorous and predatory insect pests, where no herbivorous insect pests were found on sugar palm plantations, and no herbivorous insect pest attacks were found on sugar palm plants on people's plantation land. Many types of predatory insects are found in sugar palm plantations, including Hymenoptera, Coleoptera, Orthoptera, Mantodea, Dermaptera, and Diptera. These findings contribute to a deeper understanding of the ecological balance within sugar palm agroecosystems, emphasizing the potential role of natural predators in maintaining pest-free plantations and supporting sustainable agricultural practices.